Robust cellular reprogramming occurs spontaneously during liver regeneration - Yanger, Kilangsungla; Zong, Yiwei; Maggs, Lara R; Shapira, Suzanne N; Maddipati, Ravi; Aiello, Nicole M; Thung, Swan N; Wells, Rebecca G; Greenbaum, Linda E; Stanger, Ben Z (Genes & development, 2013)
Cellular reprogramming-the ability to interconvert distinct cell types with defined factors-is transforming the field of regenerative medicine. However, this phenomenon has rarely been observed in vivo without exogenous factors. Here, we report that activation of Notch, a signaling pathway that mediates lineage segregation during liver development, is sufficient to reprogram hepatocytes into biliary epithelial cells (BECs). Moreover, using lineage tracing, we show that hepatocytes undergo widespread hepatocyte-to-BEC reprogramming following injuries that provoke a biliary response, a process requiring Notch. These results provide direct evidence that mammalian regeneration prompts extensive and dramatic changes in cellular identity under injury conditions.